2018
DOI: 10.1186/s12913-018-3288-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of new rural cooperative medical scheme on the equity of health services in rural China

Abstract: BackgroundTo explore the equity in health services in the rural areas, by studying the rural residents in two counties of Ningbo City, Zhejiang.MethodsMulti-stage stratified cluster random sampling method was performed to draw the study sample. Trained investigators conducted face to face interviews using a questionnaire. Rural residents were stratified into 5 income groups. Centralized index (CI) and risk ratios (RR) were used to assess the equity in health services and the impact of the New Cooperative Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Chen et al found that the effect of NRCMS on promoting equity in health services has not been significant. 13 In contrast, the study of Feng and Liu suggests that NRCMS has a positive contribution in increasing the pro-poor inequality in health-care utilization. 14 Furthermore, a study which is conducted by Zhou et al reveals that health insurance has effectively reduced the income-related inequality in inpatient service utilization for the residents in China.…”
Section: Introductionmentioning
confidence: 96%
“…Chen et al found that the effect of NRCMS on promoting equity in health services has not been significant. 13 In contrast, the study of Feng and Liu suggests that NRCMS has a positive contribution in increasing the pro-poor inequality in health-care utilization. 14 Furthermore, a study which is conducted by Zhou et al reveals that health insurance has effectively reduced the income-related inequality in inpatient service utilization for the residents in China.…”
Section: Introductionmentioning
confidence: 96%
“…The increase in beds has enabled more patients to be effectively treated, and hospitalizations increased from 60 million in 2002 to 250 million in 2018 ( Figure 1 B). The popularity of basic medical insurance (7% of the population in 2002 increased to 96% in 2018) ( Figure 1 C) has also led to more opportunities for treatment ( Figure 2 ), especially in rural ( Chen et al, 2018 ; Dai et al, 2016 ), and the visits reached 5.5 billion in 2018 (increased nearly 160% compared to 2002).…”
Section: Resultsmentioning
confidence: 99%
“…With the development of economy, the per capita disposable income and health awareness of residents increased so that the residents would go to hospital when they were ill [19,20]. In addition, the unceasing improvement of NRCMS promoted the participation rate increasing which also resulted in the rise of hospital admissions [21,22].…”
Section: Discussionmentioning
confidence: 99%